Avaliação dos protocolos de Easy Clean na remoção de detritos dos canais radiculares. - Custódio, Vitória Zinza [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The aim of this study was to evaluate the effectiveness of different Easy Clean(EC) protocols by means of scanning electron microscopy. For that, 20 human lower premolars with curved canals were longitudinally sectioned and six hemispherical cavities was made along the vestibular section of each root canal. The cavities were filled with debris, except for the positive control group. 10 groups were created according to the final irrigation protocol: Group 1- positive control (no debris and no final irrigation); Group 2- negative control (with debris and without final irrigation); Group 3- conventional irrigation with 2.5% sodium hypochlorite (NaOCl); Group 4- conventional irrigation with 17% ethylenediaminetetraacetic acid (EDTA) followed by NaOCl; Group 5- EC with 3 cycles of 20 seconds (NaOCl-NaOCl-NaOCl); Group 6- EC with 3 cycles of 20 seconds (NaOCl-EDTA-NaOCl); Group 7- EC with a 60 seconds cycle (NaOCl); Group 8- EC with a 180 seconds cycle (NaOCl); Group 9- EC with 2 cycles of 60 seconds (EDTA-NaOCl); Group 10- EC with 2 cycles of 60 seconds (NaOCl-EDTA).The analysis of the specimens was performed by Scanning Electron Microscope (SEM) and was done by scoring: 1 - no debris in the dentinal tubules, 2- debris covering an area smaller than 50% of the dentinal tubules; 3- debris covering an area greater than 50% of the dentinal tubules; 4 – dentinal tubules covered entirely by debris. For statistical analysis, the kappa test was used for inter-examiner concordance, while the Kruskall-Wallis, Dunn and Friedman tests was used to compare the groups. The positive results that the groups of irrigation with Easy Clean using only NaOCl (groups 5, 7 and 8) gave positive results, being superior to the groups of conventional irrigation (groups 3 and 4) and negative control (group 2). The installation groups with Easy Clean associated with the use of EDTA (groups 6, 9 and 10) are unchanged to the positive control group in the removal of debris from the root canal and in the exposure of the dentinal tubules. Based on this study, it can conclude that groups 6, 9 and 10 were the most effective in removing debris and exposing the dentinal tubules of the root canal.

O objetivo desse trabalho foi analisar diferentes protocolos de irrigação final com Easy Clean (EC) em movimento rotatório na remoção de detritos do canal radicular. Para isso, 20 pré-molares inferiores humanos de canais curvos foram seccionados longitudinalmente e seis cavidades hemiesféricas foram realizadas ao longo da secção vestibular de cada canal radicular. Essas cavidades foram preenchidas com detritos, exceto para o grupo controle positivo. Foram criados 10 grupos de acordo com o protocolo de irrigação final: Grupo 1- controle positivo (sem detritos e sem irrigação final); Grupo 2- controle negativo (com detrito e sem irrigação final); Grupo 3- irrigação convencional com hipoclorito de sódio 2,5% (NaOCl); Grupo 4- irrigação convencional com ácido etilenodiamino tetra-acético 17% (EDTA) seguido de NaOCl; Grupo 5- EC com 3 ciclos de 20 segundos (NaOCl-NaOCl-NaOCl); Grupo 6- EC com 3 ciclos de 20 segundos (NaOCl-EDTA-NaOCl); Grupo 7- EC com um ciclo de 60 segundos (NaOCl); Grupo 8- EC com um ciclo de 180 segundos (NaOCl); Grupo 9- EC com 2 ciclos de 60 segundos (EDTA-NaOCl); Grupo 10- EC com 2 ciclos de 60 segundos (NaOCl-EDTA). A análise dos espécimes foi efetuada utilizando Microscópio Eletrônico de Varredura (MEV) e atribuído scores. Para análise estatística foi utilizado o teste de Kruskall-Wallis. Os resultados mostraram que os grupos de agitação com Easy Clean utilizando apenas NaOCl (grupos 5, 7 e 8) deram resultados positivos, sendo superior aos grupos de irrigação convencional (grupos 3 e 4) e controle negativo (grupo 2). Os grupos de agitação com Easy Clean associado ao uso de EDTA (grupos 6, 9 e 10) se mostraram semelhante ao grupo controle positivo na remoção de detritos do canal radicular e na exposição dos túbulos dentinários. Com base neste estudo, pode-se concluir que os grupos 6, 9 e 10 foram os mais eficazes na remoção de detritos e exposição dos túbulos dentinários do canal radicular.
Evaluation of Easy Clean protocols on the removal of root canal debris.
Keywords: Dental pulp cavity; Hipoclorito de sódio; Cavidade pulpar